2015
DOI: 10.1517/17425247.2015.1080686
|View full text |Cite
|
Sign up to set email alerts
|

Drug release, preclinical and clinical pharmacokinetics relationships of alginate pellets prepared by melt technology

Abstract: Calcium acetate was required as a disintegrant more than as a crosslinking agent clinically to promote pellet fragmentation, fast gastrointestinal transit and drug release in intestinal medium, and intestinal-specific drug bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that the alginate gel is characterized by a high level of porosity and rapid drug release profiles. , Thus, the successful application of alginate–insulin nanoparticles via gastric gavage may not necessarily translate to an equivalent therapeutic outcome had the nanoparticles been administered perorally. On this note, the present investigation aimed to microencapsulate the alginate–insulin nanoparticles into alginate beads coated with an oleic acid-conjugated chitosan layer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the alginate gel is characterized by a high level of porosity and rapid drug release profiles. , Thus, the successful application of alginate–insulin nanoparticles via gastric gavage may not necessarily translate to an equivalent therapeutic outcome had the nanoparticles been administered perorally. On this note, the present investigation aimed to microencapsulate the alginate–insulin nanoparticles into alginate beads coated with an oleic acid-conjugated chitosan layer.…”
Section: Introductionmentioning
confidence: 99%